2005
DOI: 10.1002/ajmg.b.30216
|View full text |Cite
|
Sign up to set email alerts
|

DNA pooling analysis of ADHD and genes regulating vesicle release of neurotransmitters

Abstract: ADHD is one of the most prevalent, and heritable behavioural disorders in childhood. Genetic associations have been reported with polymorphic variants within or near to dopamine pathway genes. Recently snap-25 has also shown association with ADHD in several datasets. We therefore investigated other genes that produce proteins that interact with SNAP-25 in the mechanism of vesicular release of neurotransmitters at the synapse. A total of 106 SNPs were screened for minor allele frequency greater than 5% and 61 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Reuter et al [88] found that higher symptom scores were associated with the MET/MET genotype in German adults who were healthy or diagnosed with eating or substance use disorders and Gothelf [89] documented a 5-fold increased risk for the MET allele in 55 subjects with velocardiofacial syndrome and comorbid ADHD relative to those without comorbid ADHD. The lack of significant results from the IMAGE project [90] is consistent with the negative meta-analysis conducted by Cheuk et al [22]. Although these association studies rule out a simple role for the Val108Met polymorphism in the etiology of ADHD, it is of note that COMT hass been found to be highly upregulated in a rat model of ADHD caused by prenatal exposure to polychlorinated biphenyls [91].…”
Section: Association Studies Of Catecholaminergic Genessupporting
confidence: 64%
“…Reuter et al [88] found that higher symptom scores were associated with the MET/MET genotype in German adults who were healthy or diagnosed with eating or substance use disorders and Gothelf [89] documented a 5-fold increased risk for the MET allele in 55 subjects with velocardiofacial syndrome and comorbid ADHD relative to those without comorbid ADHD. The lack of significant results from the IMAGE project [90] is consistent with the negative meta-analysis conducted by Cheuk et al [22]. Although these association studies rule out a simple role for the Val108Met polymorphism in the etiology of ADHD, it is of note that COMT hass been found to be highly upregulated in a rat model of ADHD caused by prenatal exposure to polychlorinated biphenyls [91].…”
Section: Association Studies Of Catecholaminergic Genessupporting
confidence: 64%
“…Recently, several additional variants of the noradrenaline transporter have been associated to ADHD [20, 22, 65, 83, 84, 86, 95, 191, 192] and require further attention and more elaborate analyses. One example of such an analysis was already described above, suggesting that variations in the noradrenaline transporter may show effects in the presence of specific variants in the COMT gene (and vice versa), only [140].…”
Section: Noradrenergic Systemmentioning
confidence: 99%
“…Researchers have mainly studied a functional 48bp variable number of tandem repeats (VNTR) in exon 3 of the DRD4 gene, and have found consistent associations between ADHD and the 7 repeat allele (7R), which is related to decreased functional activity [Asghari et al, ], in both children and adults [Johansson et al, ; Gizer et al, ; Nikolaidis and Gray, ; Sánchez‐Mora et al, ; Tovo‐Rodrigues et al, , 2013]. A second polymorphism in DRD4 , a 120bp duplication located 1.2 kb upstream from the translation start codon that may play a role in transcriptional activity [Paredes et al, ], has also been studied in ADHD with controversial results [Barr et al, ; D'Souza et al, ; Brookes et al, ; Bidwell et al, , Hasler et al, ]…”
Section: Introductionmentioning
confidence: 99%